2021
DOI: 10.1186/s13613-021-00881-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term health-related quality of life, physical function and psychological consequences of severe COVID-19

Abstract: Background Survivors of severe COVID-19 are at risk of impaired health-related quality of life (HRQoL) and persistent physical and psychological disability after ICU and hospital discharge. The subsequent social burden is a major concern. We aimed to assess the short-term HRQoL, physical function and prevalence of post-traumatic stress symptoms of invasively mechanically ventilated COVID-19 patients treated in our ICU. Methods Prospective, observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 30 publications
3
52
2
Order By: Relevance
“…On the other hand, in our study population DLCO impairment degree, which is the most reported respiratory functional impairment in post-COVID syndrome, was not associated with ARDS severity. Even if potentially controversial, this result confirms that COVID-19 patients requiring intensive care and IMV can fully recover [32,33].…”
Section: Persistent Dyspnea and Pulmonary Function Testssupporting
confidence: 54%
“…On the other hand, in our study population DLCO impairment degree, which is the most reported respiratory functional impairment in post-COVID syndrome, was not associated with ARDS severity. Even if potentially controversial, this result confirms that COVID-19 patients requiring intensive care and IMV can fully recover [32,33].…”
Section: Persistent Dyspnea and Pulmonary Function Testssupporting
confidence: 54%
“…The pandemic COVID-19 caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus has dramatically affected human life and the world economy with more than 178 million confirmed cases and 3.8 million deaths (June 2021, WHO COVID-19 dashboard). At the same time, it has launched a challenge to researchers all over the world to identify the molecular features of viral infection and propagation in order to find the most appropriate therapy [100][101][102][103][104]. The SARS-CoV-2 virus is characterized by high infectivity and mutability, lethality and variant morbidity [105].…”
Section: The Pandemic Covid-19 and Molecular Basis Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) rates are particularly high among patients with more severe COVID-19-related symptoms ( Chamberlain et al, 2021 ; Greenberg and Rafferty, 2021 ). Specifically, patients who require admission to Intensive Care Units (ICU) for treatment of acute COVID-19 are at increased risk of developing post-traumatic symptoms ( Carenzo et al, 2021 ; Herridge et al, 2011 ). Indeed, it is known that traumatic experiences confronting the individual unexpectedly with death, a danger to life, or a threat to physical and mental integrity may cause difficulty regulating emotional states and tolerating negative emotions ( La Rosa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%